REKONTEKSTUALISASI TUJUAN PENDIDIKAN ISLAM DI ERA MODERN: TELAAH TAFSIR AL-WASITH & AL-IBRIZ ATAS QS. ALI IMRAN 187-191 - Hasibuan, Ahmad Suhendra; Mubin, Khoirul; Bangun, Khairuddin (Raudhah - Proud To Be Professional, 2024)
The purpose of this research is to recontextualise the purpose of Islamic education in the modern era in the perspective of the Qur'an, especially Surah Ali Imran verses 187-191, using Tafsir Al-Wasith and Tafsir Al-Ibriz. This research uses library research method with descriptive qualitative approach. The results show that the recontextualisation of the objectives of Islamic education in the modern era includes several main aspects, namely: (1) conveying and practising the truth, (2) creating reform and happiness, (3) strengthening the spiritual dimension and belief in the existence of God, (4) increasing critical reasoning, and (5) integrating religion and science. Thus, individuals who have a high level of education are expected to not only have a strong spiritual dimension and always remember the existence of God, but also have a high intellect in order to avoid the distortion and dichotomy of science.